The use of didactic methods applied in the teaching and learning of the pronunciation of the english language - Suquinagua Ramón, Nellely Daniane; Leon Lucero, Braulio Andres (Machala, Utmachala, 2023)
The present investigation addresses the problems that students present in the English language as a foreign language, in terms of pronunciation. On this basis, the use of virtual didactic resources that contribute to the improvement and strengthening of pronunciation in tenth grade students is implemented. Parallel year "A" of the Carmen Mora de Encalada School in the city of Pasaje. The pedagogical, didactic and psychological foundations that allowed the elaboration and application of the pedagogical proposal composed of a system of exercises through the didactic method using flashcards are considered. In this way, the system of exercises contributes significantly to the teaching-learning process of the English language, benefiting the students of the educational institution. This research is based on a quantitative methodological paradigm, under an experimental design. In addition, theoretical and empirical methods (interview, diagnostic test) were used to collect data that allow organizing the information for its study in response to and verification of the proposed hypothesis.
La presente investigación aborda la problemática que presentan los estudiantes en el idioma inglés como lengua extranjera, en cuanto a la pronunciación. Sobre esta base se implementa el uso de recursos didácticos virtuales que contribuyan al mejoramiento y fortalecimiento de la pronunciación en los estudiantes de décimo año paralelo “A” del Colegio Carmen Mora de Encalada en la ciudad de Pasaje. Se consideran los fundamentos pedagógicos, didácticos y psicológicos que permitieron la elaboración y aplicación de la propuesta pedagógica compuesta de un sistema de ejercicios a través del método didáctico usando flashcards, De tal manera, el sistema de ejercicios aporta significativamente en el proceso de enseñanza aprendizaje del idioma inglés beneficiando a los estudiantes de la institución educativa. Esta investigación se basa en un paradigma metodológico cuantitativo, bajo un diseño experimental. Además, se utilizaron métodos teóricos y empíricos (entrevista, prueba diagnóstica) para la recolección de datos que permiten organizar la información para su estudio en respuesta y verificación de la hipótesis planteada.
Keywords: SISTEMA DE EJERCICIO; METODO DIDACTICO; PROCESO DE ENSEÑANZA-APRENDIZAJE; PRONUNCIACION; FLASHCARD